Clinical, pathological genetics and intratumoral immune milieu of serrated adenocarcinoma of the colon. Issue 3 (20th July 2022) - Yılmaz, Osman; Crabbe, Andrew; Neyaz, Azfar; Pankaj, Amaya; Lee, Soo Hyun; Hosseini, Sahar; Rickelt, Steffen; Cerda, Sandra; Zhao, Qing; Leijsen, Lieve; Dineaux, Anne; Shroff, Stuti G; et al.
Abstract: Background: Serrated adenocarcinoma (SAC), a recognised WHO variant of colonic adenocarcinoma, is the purported end‐product of serrated neoplasia. However, the diagnosis of SAC is infrequently rendered, and little is known about its prognosis, immune microenvironment and molecular alterations. Materials and methods: We assessed 903 consecutive colon carcinomas and recognised tumours with ≥ 5% ( n  = 77) serrated and ≥ 50% serrated patterns ( n  = 13). We assessed precursor polyps and synchronous polyps. We recorded demographic/clinical parameters, histological features and mismatch repair (MMR) status. We performed immunohistochemistry and quantification on tissue microarray for HLA class I/II proteins, B2MG, CD8, CD163, LAG3, FoxP3, PD‐L1 and BRAF V600E. Results: We identified ≥ 5% epithelial serration prevalence in 8.5% of cases and ≥ 50% epithelial serration prevalence in 1.4% of cases. Precursor lesions were present in 21.4% of cases; these were mostly tubular adenomas with two traditional serrated adenomas identified. SAC with ≥ 5% serrations exhibited lower numbers of CD8‐positive lymphocytes ( P  = 0.002) and lower B2MG expression ( P  = 0.048), although neither value was significant at ≥ 50% serration threshold. There was no difference in HLA class I/II, or PD‐L1 expression on tumour cells and no difference in PD‐L1, LAG3, FoxP3 and CD163 expression on immune cells. There was no association with MMR status, or BRAFV600E relative to conventional adenocarcinoma. There was improved disease‐specific survival on univariate (but not multivariate) analysis between carcinomas with serrated pattern and non‐mucinous conventional colonic carcinomas at ≥ 5% epithelial serrations ( P  = 0.04). Conclusion: SAC category shows a limited impact on survival, and this phenotype may harbour a unique immunological milieu. Abstract :